Examining the impact of work environment, compensation, working hours, and empowerment on hotel employees’ performance - Md Yuslan, Muhammad Farhan; Mohd Faudzi, Muhammad Izz Iman; Noorkhizan, Mohd Hazrin Iman; Abdul Latip, Muhammad Safuan; Mahusain, Muhammad Afnan (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
This study investigates the relationship between employee engagement factors and job performance in the hotel industry. A probability sampling approach was employed, and data were collected through a structured, closed-ended questionnaire from 384 hotel employees in Shah Alam, Selangor, representing the front office, food and beverages, and housekeeping departments. The results indicate that compensation and benefits and working hours exert significant positive effects on employee job performance, with working hours identified as the strongest predictor. Conversely, the work environment and employee empowerment showed no statistically significant impact on job performance. These findings suggest that tangible job conditions, particularly fair compensation and manageable working hours, play a more critical role in enhancing employee performance compared to environmental or empowerment-related factors. The study provides practical implications for hotel managers and human resource practitioners in designing policies to strengthen employee engagement and optimise organisational performance.